PILOT EVALUATION OF UTILISING MENTAL HEALTH NURSES IN THE MANAGEMENT OF AMBULANCE SERVICE PATIENTS WITH MENTAL HEALTH PROBLEMS. Issue 9 (18th August 2016) - Irving, Andy; O'Hara, Rachel; Johnson, Maxine; Harris, Angela; Baker, Kieran
Abstract : Background: The urgent and emergency care review advocates new models of care to provide safer, faster and better care. Available evidence highlights scope for improvement in the delivery of care for patients calling 999 with mental health problems. The purpose of this abstract is to describe an ongoing initiative in Yorkshire Ambulance Service utilising specialist triage by mental health nurses in the Emergency Operations Centre (EOC) since December 2014. Methods: An exploratory mixed methods evaluation was conducted. Interviews (n=12) with key stakeholders in the ambulance service were conducted to explore their experiences of service provision for patients with mental health problems and the impact of introducing Mental Health Nurse triage in the EOC. Interview data was coded and thematically analysed to identify key issues around service delivery for patients with mental health problems. Routine data from ambulance service computer aided dispatch was used to examine impact on patient care and resource allocation. Results: Initial findings indicate that access to mental health nurses in the EOC reduced the ambulance response rate by clinically triaging calls for patients with mental health problems and only sending a resource where appropriate. Staff interviews revealed the developmental process and challenges involved in implementing the mental health triage initiative, for example, recruitment, training and governance. Staff perceptions of the initial positive impact of the mental health nurses include the delivery of more appropriate patient care and reduced anxiety for staff managing calls that now have access to specialist support. Conclusions: Despite the relatively short time period since the inception of this initiative, the preliminary findings from this pilot evaluation suggest a positive impact on service delivery from a patient and organisational perspective. Lessons learned from the implementation of this initiative and its progression are potentially informative for other Ambulance Service Trusts considering adopting a similar approach.